GAZ AND GAS CONDENSATE WORK AND PREPARATION SYSTEMS METHODS OF USE ANALYSIS - Abdirazakov Akmal Ibrahimovich,; Namozov is the son of Ogabek Mahmud, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION One  of  the  most  important  components  of  the  country's  gas  industry development strategy is the State Program for the Creation of a Unified System of Gas Production, Transportation and Supply in 2007. Solving the problems of effective gas pipeline management includes a set of tasks for modeling and optimal planning of the operating modes of the entire chain of gas pipeline technological facilities. The solution to these problems is based on the integration of models of facilities managed by the gas production company, from wells to the compression compressor station (SCS). Currently, there is a significant gap between the capabilities of modern gas production,  gathering  and  processing  modeling  systems,  such  as  PIPESIM,  OLGA (Schlumberger)  and  others,  and  the  needs  of  subsoil  users  to  solve  problems  of modeling and controlling the operating modes of objects that perform these processes as a single system. These gaps are mainly due to the lack of mathematical models and algorithms  for  modeling  stable  and  unstable  operating  modes  of  the  entire  gas production organization, which usually includes wells, gas well networks, field gas gathering  networks  (GFG),  gas  primary  treatment  facilities  (GPTP),  inter-field  gas gathering  collectors  (IGGC),  integrated  gas  complex  treatment  facilities  (IGCP), compression compressor stations (SCS) and main gas pipelines (MGP). Thus , the development of mathematical methods and algorithms that solve the technological  problems  of  modeling  and  management  of  gas  production  complex regimes is currently an urgent task.